2023
DOI: 10.1111/aor.14549
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of mitral regurgitation in patients undergoing left ventricular assist device deployment: A systematic review and meta‐analysis

Abstract: BackgroundLeft ventricular assist devices (LVADs) represent an important therapeutic option for patients progressing to end‐stage heart failure. LVAD has previously been shown to have a promising role in improving mitral regurgitation (MR). Nevertheless, the prognostic value of preoperative uncorrected MR in this population remains unclear.MethodsA systematic database search with meta‐analysis was conducted of comparative original articles of patients with preoperative mild MR (Grade 0–I) versus moderate–sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…8,[19][20][21][22] This is believed to be a result of improving the haemodynamics of the left ventricle thus lowering the left ventricular enddiastolic diameter (LVEDD) and therefore reducing the severity of MR. 23 It is most likely because of this, that we did not find increased survival in the LVAD + MVR group. Whilst our recently published meta-analysis showed that the degree of pre-operative MR does not appear to affect mortality in patients receiving LVAD, 24 the same cannot be said for post-operative MR with several studies linking it to worse clinical outcomes, 25,26 a conclusion which was also reached by the recently published study by Loforte and colleagues. 27 Interestingly, the study by Loforte et al 27 surprisingly demonstrates that LVAD implantation in patients with significant preoperative MR without concomitant mitral valve surgery leads to better survival and morbidity outcomes compared to those with mild or no MR.…”
Section: Mortality Outcomesmentioning
confidence: 91%
“…8,[19][20][21][22] This is believed to be a result of improving the haemodynamics of the left ventricle thus lowering the left ventricular enddiastolic diameter (LVEDD) and therefore reducing the severity of MR. 23 It is most likely because of this, that we did not find increased survival in the LVAD + MVR group. Whilst our recently published meta-analysis showed that the degree of pre-operative MR does not appear to affect mortality in patients receiving LVAD, 24 the same cannot be said for post-operative MR with several studies linking it to worse clinical outcomes, 25,26 a conclusion which was also reached by the recently published study by Loforte and colleagues. 27 Interestingly, the study by Loforte et al 27 surprisingly demonstrates that LVAD implantation in patients with significant preoperative MR without concomitant mitral valve surgery leads to better survival and morbidity outcomes compared to those with mild or no MR.…”
Section: Mortality Outcomesmentioning
confidence: 91%